Christians and Muslims in the Middle Ages From Muhammad to Dante - Frassetto, Michael 1961- (Lexington Books, 2019)
This study examines relations between Muslims and Christians during the Middle Ages. The author argues that the relationship between the two faiths was essential to the creation of the cultural and religious traditions that defined each faith.